2022
DOI: 10.1017/aae.2022.23
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Management of Irrigation Water from Aquifer and Surface sources

Abstract: We explore the economic merits of on-farm water storage with tailwater recovery systems to reduce aquifer depletion in a region with expanding irrigated acreage and substantial off-season precipitation. Gains are substantial on a broad scale and long planning horizon, including more than $4 billion in producer surplus, 5 million acre-feet of conserved groundwater, and land capitalization of $24 per acre. Sensitivity analyses provide insights with respect to the impact of discount rates, rainfed returns, return… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…where 𝑎 𝑖 and 𝑏 are positive constants. This represents diminishing returns to production, which accords with most production practices as reported in many groundwater literature (e.g., Gisser & Sánchez, 1980;Provencher & Burt, 1994;Gardner et al, 1997;Msangi & Hejazi, 2022;Quintana-Ashwell & Gholson, 2022). Based on this, we introduce user heterogeneity by differentiating parameter 𝑎 𝑖 s. Although we do not differentiate parameter 𝑏 to obtain analytical solutions for the dynamic game, this differentiation allows us to cover a broad range of heterogeneity in terms of production scale and technology.…”
Section: Model Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…where 𝑎 𝑖 and 𝑏 are positive constants. This represents diminishing returns to production, which accords with most production practices as reported in many groundwater literature (e.g., Gisser & Sánchez, 1980;Provencher & Burt, 1994;Gardner et al, 1997;Msangi & Hejazi, 2022;Quintana-Ashwell & Gholson, 2022). Based on this, we introduce user heterogeneity by differentiating parameter 𝑎 𝑖 s. Although we do not differentiate parameter 𝑏 to obtain analytical solutions for the dynamic game, this differentiation allows us to cover a broad range of heterogeneity in terms of production scale and technology.…”
Section: Model Formulationmentioning
confidence: 99%
“…The major methodological limitations of this paper are as follows. First, similar to almost all existing groundwater studies (e.g., Gisser & Sánchez, 1980;Provencher & Burt, 1994;Gardner et al, 1997;Msangi & Hejazi, 2022;Quintana-Ashwell & Gholson, 2022), we used a quadratic form for the benefit function (production function), which enabled us to derive simple analytical and even reduced-form solutions. Although we believe that our conclusions are not affected by function types, as long as they allow for diminishing marginal benefits, an assumption that accords with most production practices, we can numerically examine other types of benefit functions in future studies.…”
Section: Numerical Illustrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rainwater harvesting takes attention by individual builgings from the roof top or gardens for individual use. A recent study by Quintana-Ashwell et al [2022] showed how much can be gained by efficient irrigation through on-farm storage systems from the techno economical perspective. In addition, "road rain water harvesting" appears as an alternative as another possible way of harvesting rain water [Steenbergen et al 2018].…”
Section: Introductionmentioning
confidence: 99%